2022
DOI: 10.1002/jcp.30809
|View full text |Cite
|
Sign up to set email alerts
|

Extending applications of AFM to fluidic AFM in single living cell studies

Abstract: In this article, a review of a series of applications of atomic force microscopy (AFM) and fluidic Atomic Force Microscopy (fluidic AFM, hereafter fluidFM) in single-cell studies is presented. AFM applications involving single-cell and extracellular vesicle (EV) studies, colloidal force spectroscopy, and single-cell adhesion measurements are discussed. FluidFM is an offshoot of AFM that combines a microfluidic cantilever with AFM and has enabled the research community to conduct biological, pathological, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 182 publications
(314 reference statements)
0
13
0
Order By: Relevance
“…(B) Representative immunofluorescence stainingof VE-cadherin in recipient PMECs after exposure to ECExos, R -ECExos, and R -ECExos that were treated with 20 μg/mL ribonuclease (RNase) in the presence or absence of 0.1% saponin as we reported for ECExos from BMECs( 61 ). (C) The lateral binding forces (LBFs) were assessed by Fluid AFM-measured detachment works in recipient PMECs after exposure to ECExos, R -ECExos, and R -ECExos that were treated with 20 μg/mL ribonuclease (RNase) in the presence or absence of 0.1% saponin as reported( 76, 85 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) Representative immunofluorescence stainingof VE-cadherin in recipient PMECs after exposure to ECExos, R -ECExos, and R -ECExos that were treated with 20 μg/mL ribonuclease (RNase) in the presence or absence of 0.1% saponin as we reported for ECExos from BMECs( 61 ). (C) The lateral binding forces (LBFs) were assessed by Fluid AFM-measured detachment works in recipient PMECs after exposure to ECExos, R -ECExos, and R -ECExos that were treated with 20 μg/mL ribonuclease (RNase) in the presence or absence of 0.1% saponin as reported( 76, 85 ).…”
Section: Resultsmentioning
confidence: 99%
“…2B ). Furthermore, measuring the lateral binding forces (LBFs) between PMECs, the biomechanical nature of the endothelial barrier( 76, 85 ), suggested that PMEC paracellular barrier dysfunction occurs after treatment with R -ECExos ( Fig. 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, measuring the lateral binding forces (LBFs) between homogenous cells in response to different stimuli is crucial to understanding the precise biomechanical mechanism underlying intercellular barrier dysfunctions, which is a major outcome of host responses to infections and inflammation. A new biomechanical strategy using AFM-based fluidic force micropipette technology (fluidic AFM) can directly measure live EC-to-EC LBFs in EC monolayers ( Supplementary Figure 4 ) ( 58 , 59 ). We found that the LBFs between living BMECs were reduced after treatment with R -ECExos ( Figure 5D ), providing direct evidence of the biomechanical nature of the endothelial barrier dysfunction during rickettsial infections.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the measurement of lateral binding forces (LBFs) between BMECs is crucial in evaluating the precise biomechanical features underlying BBB dysfunctions. To directly measure the LBFs between live BMECs Employing, a new biomechanical strategy using fluidic force microscopy (fluidic AFM) 97,100,101 was employed (. The results revealed that the LBFs between live BMECs were reduced in a dose-dependent manner after 72-hr treatment with AD-Exos (Fig.…”
Section: Ad Circulating Exosomes (Ad-exos) Induce Barrier Dysfunction...mentioning
confidence: 99%